Administrative offences law (constitutional prospects of codification) - Sergey D. Knyazev; Konstantin V. Aranovskiy; Yuri M. Danilov (Правоприменение, 2020)
The subject of the research is the problems of constitutional law enforcement of administrative offences legislation, taking into account the prospects for its new codification.The purpose of the article is confirmation or confutation of the hypothesis that the effectiveness of the new Code of administrative offences depends on whether the legal positions of the Constitutional Court of the Russian Federation on the principles of administrative responsibility will be taken into account when drafting it.The authors use methods of complex analysis, synthesis, as well as formal-legal method of interpretation of Constitution, legislation on administrative offences and judicial decisions of Russian Constitutional Court.The main results and scope of their application. The administrative torts law in Russia is expected to pass through the total review up to the grounds of its codification in close future. The article presents initial positions of that changes within basic frames produced by Russian Constitutional Court. Its case-law has already invaded into many spheres and details in respective sphere of legal rules and also prescribed a lot for their future. This case-law yet is necessarily made within its inherent range for it is ever constrained procedurally by content of actions and cases to be settled. However Russian administrative torts law is destined for reformation in new code-making in view of constitutional case-law and in order to do better with neighbor spheres of legal responsibility. Disputable matters of administrative liability, the company’s responsibility with psychical fiction on its fault (corporative thinking, wishing, desire, diligence), substantial and procedural equity etc. are described and discussed in the article as to the administrative law of torts on in its constitutional dimension.Conclusions. The Code of administrative offences of the Russian Federation does not fully meet the legal needs of society. Work on real improvement of this code will continue, therefore, legal science should be more strongly and persistently to implement in legislative practice constitutional ideas about improvement of codification and ensuring unity of legal space of the country. In particular, it is necessary to settle the debatable aspects of tort liability, the guilt of legal entities when it is addressed by fiction to the phenomena of the psyche (thinking, goals, will, caution), the constitutional and legal foundations of justice in the field of administrative penalties, procedural enforcement of rights and freedoms, etc.